Impact Of Tobacco Control Policies On Cigarette Consumption In Malaysia - Norashidah Mohamed Nor; Wency Kher Thinng Bui; Judhiana Abd. Ghani; Noraryana Hassan; Nizam Baharom (UNIMAS, 2024)
Indexed by Scopus/MyCite